Global research trends and basis of venous/lymphatic malformations during 2003–2023: a bibliometric study over two decades - Liu, Hongyuan; Zhu, Jun; Chen, Hui; Lin, Xiaoxi (Frontiers in Medicine, 2025)
IntroductionVenous/lymphatic malformations (VM/LM) represent a group of vascular anomalies that share similarities in diagnosis, classification, management, and pathogenesis. Despite growing research interest, no comprehensive bibliometric analysis has been conducted to map the knowledge landscape and evolution of VM/LM studies.MethodsWe searched the Web of Science Core Collection database for VM/LM-related publications from January 2003 to December 2023. multiple analytical tools including VOSviewer, CiteSpace, and R package ‘bibliometrix’ were used to analyze publication trends, collaboration networks, and research hotspots.Results4,747 publications with 57,893 references were enrolled and analyzed. The number of publications is growing generally and erupted in 2019. The USA, China, and Japan are the top 3 countries in publication. The main study centers are scattered in the USA, Europe, China, and Japan. Fishman SJ published most. Vikkula M was cited most. Journal of Pediatric Surgery published and was cited most. The knowledge basis of VM/LM contains a wide range of concepts including classification/differential diagnosis, genetic causes, Sirolimus treatment, localized intravascular coagulopathy, and percutaneous treatment. The topic trend mainly changed after 2019 to genetic study and targeted therapy.DiscussionThis is the first bibliometric analysis of VM/LM research demonstrating the field’s rapid growth and shifting research hotspots. Four key future directions emerged: molecular-level diagnosis and classification, precision targeted therapy, advanced sclerotherapy techniques, and artificial intelligence applications. International collaboration between countries and centers needs to be strengthen. These findings provide an objective foundation for future VM/LM investigations.